Representaciones sociales frente al riesgo de desastres en una comunidad educativa de Bogotá: un proceso formativo a través de ambiente virtual de aprendizaje - Castillo Cortes, Armin Nankincoll (Universidad Antonio Nariño, 2023)
This research describes the appropriation of disaster risk concepts in an educational community through the design and implementation of the virtual learning environment called "Prevention and Safety". It was carried out with a qualitative, descriptive approach based on a case study. The objective was achieved in three moments: A diagnosis that allowed identifying the institution's reaction to an emergency. The design of a virtual learning environment, as a means of interactive socialization of the institution's risk management plan as well as a mechanism for various training on the subject. And description of social representations of the community regarding disaster risk management, after applying the strategy. The results show that virtual learning environment was an effective mechanism for community members (students, parents, and teachers) to generate a social representation of risk.